Music Computer Technologies, Supply Chain Strategy and Transformation Processes in Socio-Cultural Paradigm of Performing Art: Using Digital Button Accordion - Irina B.Gorbunova; Natalia N. Petrova (International Journal of Supply Chain Management, 2019)
The article traces the transformation of the socio-cultural paradigm of button accordion performing as a dichotomy of traditional and innovative cultural directions. The authors carry out a diachronic analysis of the formation and development of electronic button accordion playing in the XX-XXI centuries, analyzing the psychoacoustic transformation of the socio-cultural perception of the musical electronic environment, identify the causes of social devolution of electronic button accordion in the XX century, and carry out a historical and cultural analysis of the process of the revival of performing on various modifications of electronic harmonicas in Russia. Performance on a digital button accordion is seen as a logical outcome of the evolution of the instrument accordion complex and the socialization of instrumentation in the new socio-economic conditions of the digital society. The article reveals the features of the formation of performance on a digital button accordion in the modern high-tech process of musical creativity, which opens up great prospects for contemporary forms of cultural and socio-cultural activity of a modern musician. Music and computer technologies are considered as an integral part of the cognitive-creative component of the work of the modern musician of the digital age.